"I am 22 Million" : reading Winnie Madikizela as the intellectual face of anti-apartheid popular struggle - Valela, Ntombizikhona (Rhodes University, Faculty of Humanities, Department of History, 2017)
The purpose of this research is to read Winnie Madikizela Mandela as an intellectual. Through this research I want to examine whether Madikizela Mandela emerges from an intellectual tradition influenced by the political and intellectual discourse that existed at the time within the country such as the ideology of the African National Congress (not to say that this was without external influence but I would argue that the ideology of the ANC evolved to fit the domestic politics of the day), the Civil Rights Movement, the Black Panther Party and Black Consciousness. Through trying to understand Madikizela Mandela's intellectual journey this thesis will explore the larger question of intellectual production. Lewis Gordon argues that it is often presumed that theory is north and experience is south.1 As a result black people are often excluded from being possible intellectuals and shapers of intellectual discourse but are rather relegated to the categories of 'actors' rather than thinkers. The point of departure of my research will be through Winnie Madikizela-Mandela's image as it provides a clue into the type of intellectual influences and ideologies that she subscribed to. This flows from Charles R. Garoian and Yvonne M. Gaudelius' "The Spectacle of Visual Culture" where they argue for images teaching us what to see and think.2 Winnie Madikizela Mandela was a frequently photographed person and it is through these images that we witness an evolution in the way she presented herself which, as this research argues, is influenced by certain intellectual traditions that guide the black liberation struggle. In What's My Name: Black Vernacular Intellectuals, Grant Farred explores the role of clothing in the conveying of intellectualism influenced by a certain ideology. Therefore I argue that Winnie Madikizela's iconicity is more than conventional standards of beauty, or her link to her husband Nelson Mandela. It is rather a tool that she uses to convey an ideology and this complements that which she says when she chooses to speak.
Keywords: Uncatalogued